Correlation of Home Environment Among Personality and Academic Performance of Undergraduates in Cambodia - Sereyrathana Heng; Bunhoeun Chhourn; Ratana Loch; Sarom Mok; Sereyrath Em (Journal of General Education and Humanities, 2025)
English language performance at higher education level is very important. To improve the learning performance of undergraduates, it is essential to identify the associated factors that could contribute to this enhancement. Therefore, this study aims to investigate the triple dimensions, including personality, academic performance, and family relations of the undergraduates, as well as the association between these dimensions. The study used a quantitative correlational research design involving 100 samples. The data on the triple aspects was gathered through standardized questionnaires. Descriptive and inferential statistics such as Mean, Standard Deviation, Pearson Correlation Coefficient, and P-value were adopted for data analysis. The study found that the overall mean score for personality was 3.26, indicating slightly above the medium level, and the mean score for academic performance was 2.30, indicating below the medium level. The mean score for family ties was 3.99, which indicates that the family is above the medium level. In addition, the research found that the undergraduate’s academic performance and personalities were statistically and positively associated with their family relations with (r = 0.378, p = 0.000) and (r = 0.362, p = 0.000) accordingly. The findings suggested the importance of fostering positive family relations, enabling undergraduates to develop positive personalities and improve academic performance. Future studies can be conducted using bigger sample sizes.